1982
DOI: 10.1063/1.330467
|View full text |Cite
|
Sign up to set email alerts
|

Electron irradiation effects in p-type GaAs

Abstract: Ion irradiation damage in ntype GaAs in comparison with its electron irradiation damageDeep level centers produced by I-MeV electron irradiation at room temperature onp-type GaAs (liquid-and vapor-phase epitaxial layers) have been studied by means of Deep Level Transient Spectroscopy and Deep Level Optical Spectroscopy. Activation energies, thermal and optical photo ionization cross sections, and introduction rates have been measured for the main defects. The trap HI is shown to have an introduciton rate (0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The absorption band centered at 1.3µm covers the range of interest and grows linearly with the irradiation dose (Fig.5). We attribute this absorption band to the photoemission of holes from the H3 defect, the photoionization cross-section spectrum of which has been determined by Deep Level Optical Spectroscopy experiments in p-type crystals [20]. This spectrum, presented in Figure 6, corresponds exactly to the absorption spectra we measure (Fig.4).…”
Section: B Absorptionsupporting
confidence: 72%
“…The absorption band centered at 1.3µm covers the range of interest and grows linearly with the irradiation dose (Fig.5). We attribute this absorption band to the photoemission of holes from the H3 defect, the photoionization cross-section spectrum of which has been determined by Deep Level Optical Spectroscopy experiments in p-type crystals [20]. This spectrum, presented in Figure 6, corresponds exactly to the absorption spectra we measure (Fig.4).…”
Section: B Absorptionsupporting
confidence: 72%
“…The defect lines found in the dot samples have activation energies and capture cross sections from an Arrhenius analysis that are similar to those reported in the literature. [23][24][25][26] The nature of these is still a topic of discussion, as they are also associated with native defects such as vacancies, interstitials, antisites, and in some cases with impurities such as Cu and Fe. Because the SK growth mode involves the strain-induced movement of GaSb to form quantum dots it is likely that stoichiometric defects will be left in the GaAs near the dots in small quantities measurable in a DLTS experiment.…”
Section: Discussionmentioning
confidence: 99%
“…First, we consider the hole trap C. Table 2 lists the summary of the trap energy and hole capture crosssection. Loualiche et al [27] reported irradiation-induced hole traps in p-type GaAs by a systematic study of the effect of 1 MeV electron irradiation at room temperature and detected a defect with the same activation energy (0.2 eV) as the C defect. Auret et al [28] reported on the electrical properties of hole traps created during irradiation of p-GaAs grown by molecular beam epitaxy (MBE).…”
Section: Discussion and Summarymentioning
confidence: 99%